Assessment of immunogenicity from galcanezumab phase 3 trials in patients with episodic or chronic migraine. (August 2020) - Martinez, James M; Hindiyeh, Nada; Anglin, Greg; Kalidas, Kavita; Hodsdon, Michael E; Kielbasa, William; Moser, Brian A; Pearlman, Eric M; Garces, Sandra
Background: This analysis characterizes the immunogenicity profile of galcanezumab, a humanized monoclonal antibody that selectively binds calcitonin gene-related peptide and inhibits its activity, in phase 3 migraine trials. Methods: Immunogenicity data were analyzed from baseline and double-blind, placebo-controlled phases of the 3-month chronic migraine study REGAIN, the 6-month episodic migraine studies EVOLVE-1 and EVOLVE-2, and from baseline and open-label phases of the 12-month chronic and episodic migraine Study CGAJ. The incidence of baseline antidrug antibodies, treatment-emergent antidrug antibodies, neutralizing antidrug antibodies, and the effect of antidrug antibody titer on pharmacokinetics and pharmacodynamics were assessed. The relationship between antidrug antibody status and efficacy was explored using average change in monthly migraine headache days. Safety analyses assessed the potential relationship between treatment-emergent antidrug antibodies and hypersensitivity events or adverse events related to injection sites. Findings: Across studies, 5.9–11.2% of patients had baseline antidrug antibodies. The incidence of treatment-emergent antidrug antibodies was 2.6–12.4% in the galcanezumab group and 0.5–1.7% in the placebo group. The majority of treatment-emergent antidrug antibodies were detected approximately 3–6 months after first study drug dose. Overall, the observed antidrug antibody titer did not impact galcanezumab concentrations, calcitonin gene-related peptide concentrations, or galcanezumab efficacy. There was no evidence that hypersensitivity events or adverse events related to injection sites were mediated by treatment-emergent antidrug antibodies. Interpretation: These data showed that immunogenicity did not impact galcanezumab concentrations, calcitonin gene-related peptide concentrations, or the efficacy and hypersensitivity profile of galcanezumab in patients with migraine.